Antimicrobial Activities and Phytochemical Investigation of Some Native Pteridophytes - S S PANDA; K SAHOO; M RANA; N C ROUT; N K DHAL (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The present investigation was carried out to screen the phytochemical and antimicrobial properties of three pteridophytes plants such as Salvinia minima Baker, Thelypteris interrupta (Wild.)K.Iwats and Marsilea minuta L. commonly found in Odisha, India. The dried and pulverized plant materials (whole) were extracted using two different solvent such as methanol and chloroform. The antimicrobial activity was demonstrated against eighteen bacterial pathogens such as Staphylococcus aureus, S.citreus, Escherichia coli, Pseudomonas sp., Pseudomonas aeruginosa, Salmonella typhii, S. paratyphii A, S. paratyphii B, Chromobacter, Enterobacter, Citrobacter fruendii, Klebsiella, Vibrio cholera, Shigella sonnie, S. boydii, Providencia, Proteus mirabilis, P. vulgaris and four fungal pathogens such as Candida albicans, Aspergillus niger, A. flavus, Rhizopus sp. Methanol extracts showed the presence of major phytoconstituents such as alkaloids, tannins, anthroquinone, steroids and terpenoids as compared to chloroform. Among the three pteridophytes, T. interrupta showed the presences of maximum phytoconstituents. The highest antibacterial activity (28mm) was observed in the methanol extract of T. interrupta against S.citreus whereas maximum antifungal activity (22mm) was observed against A. flavus in the methanol extract of S.minima.Â